Positive TPMT genotype-phenotype correlation underscores importance of TPMT genotyping for personalized thiopurine dosing - Hui-min, Neoh; Mee, Lee Looi; Muhiddin Ishak,; Mohd Ridhwan Abd Razak,; Noor Hamidah Hussin,; Zarina Latiff,; Hamidah Alias,; Rahman Jamal, (Penerbit UKM, 2012)
This study explored TPMT genotype-phenotype correlation in a group of acute lymphoblastic leukemia (ALL) patients to investigate the potential of TPMT genotyping for personalized thiopurine dosing. Genotyping for G238C (TPMT*2), G460A (TPMT*3B) and A719G (TPMT*3C) loci was determined in 89 subjects via PCR, while TPMT activity was measured using HPLC. TPMT*3C was the only mutant allele detected in 4 heterozygous carriers. These patients had significantly lower (23.0 nmol/g Hb/h) TPMT activity compared to wildtype patients (51.0 nmol/g Hb/h) (p = 0.003). Positive correlation between TPMT genotype and phenotype projects the possibility of using TPMT genotyping as a guide prior thiopurine drug administration. .